2021
DOI: 10.1080/13548506.2021.1954674
|View full text |Cite
|
Sign up to set email alerts
|

NHS frontline staff experiences of an in-house psychological support service during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has led to enormous practical and emotional challenges for healthcare workers globally, including NHS staff. Psychological support provisions have been established by an NHS healthcare trust in the North of England, including 1:1 psychological support provided by the in-house psychology team. This study sought to understand how staff experienced the service, what worked well and what could be improved. Five participants who had accessed the staff support service took part in semistructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…1 Many nurses reported feeling that the recognition they received was empty as they were being cheered by the general public that was simultaneously criticizing the validity of the virus, response to the pandemic, and legitimacy of infection control practices. 20 Over time, efforts to support frontline staff improved as formal programs, such as peer support, crisis intervention, and flexible mental health support, emerged in organizations 16,17 ; however, the relationship of meaningful recognition for individual nurses to overall organizational well-being support is not yet established.…”
Section: Culture and Climate Of Meaningful Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Many nurses reported feeling that the recognition they received was empty as they were being cheered by the general public that was simultaneously criticizing the validity of the virus, response to the pandemic, and legitimacy of infection control practices. 20 Over time, efforts to support frontline staff improved as formal programs, such as peer support, crisis intervention, and flexible mental health support, emerged in organizations 16,17 ; however, the relationship of meaningful recognition for individual nurses to overall organizational well-being support is not yet established.…”
Section: Culture and Climate Of Meaningful Recognitionmentioning
confidence: 99%
“…Results demonstrated that opportunities do exist to improve the culture and climate in organizations by: 1) noticing employees' accomplishments, 2) showing that they care, 3) taking pride in their employees' work, 4) showing concern about their well-being, and 5) responding to employees' complaints 1 . Many nurses reported feeling that the recognition they received was empty as they were being cheered by the general public that was simultaneously criticizing the validity of the virus, response to the pandemic, and legitimacy of infection control practices 20 . Over time, efforts to support frontline staff improved as formal programs, such as peer support, crisis intervention, and flexible mental health support, emerged in organizations 16,17 ; however, the relationship of meaningful recognition for individual nurses to overall organizational well-being support is not yet established.…”
Section: Culture and Climate Of Meaningful Recognitionmentioning
confidence: 99%
“… 15 However, some studies have sought to understand the experience of staff accessing and delivering interventions by using qualitative research methods. 16 , 17 …”
Section: The Phased- and Stepped-care Model Of Psychological Supportmentioning
confidence: 99%
“…According to qualitative evaluations, these spaces were highly valued, but access was dependent on buyin from managers, the ability of staff to take breaks and perceived inclusivity (Blake et al, 2021). In another trust, access to individual psychology sessions was appreciated for being driven by staff needs and fostering solidarity and a non-judgemental approach to help-seeking (Olabi et al, 2021). A number of studies investigated the effectiveness of such organisational support.…”
Section: Experience Of Organisational Supportmentioning
confidence: 99%
“…, 2021). In another trust, access to individual psychology sessions was appreciated for being driven by staff needs and fostering solidarity and a non-judgemental approach to help-seeking (Olabi et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%